HUBUNGAN DUKUNGAN SOSIAL TERHADAP PENGOBATAN KANKER PAYUDARA DI YAYASAN KANKER WISNUWARDHANA - Kevin Patar Aruan; Muhammad Atoillah Isfandiari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2015)
In the city of Surabaya, the number of patients with breast cancer is found and treated in 2014 was amounted to 709 cases. Family social support is regarded as one of the drivers of the patient for treatment. This study aimed to quantify the proportion of delay in treatment of breast cancer based on family and social support and analyzing the relationship of social support by the family against in the treatment of breast cancer cases in Yayasan Kanker Wisnuwardhana Surabaya. The study was conducted using cross sectional design using a quantitative approach. The interview was conducted on 40 patients with breast cancer. Samples were selected by simple random sampling. The results of comparison of proportions delay breast cancer treatment according to the status of family social support is 7.5: 3.6. Testing single relationship between social support by the family to delay treatment shows that there was a signifi cant relationship between social support with treatment of breast cancer (p <0.05). The conclusions are the proportion of delay in treatment more on the respondents were less lack support and there is a relationship between social support to the treatment of breast cancer cases in Yayasan Kanker Wisnuwardhana Surabaya.Keywords: breast cancer, delay treatment, social support.